The Effect of Hollow Glass Microsphere (HGM) and Iron Sand Volume Fraction on the Hardness and Wear Rate (Tribological Properties) of Composite Train Brake Blocks - Rahayu Mekar Bisono; Aulia Raiz Khoirudin; Agus Choirul Arifin; Deby Ika Hariani; Alfi Tranggono Agus Salim; M. Shafwallah Al. Aziz. R; Nyi Selfi Rosalina Apriliya (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2026)
This research addresses the wear susceptibility of pure polymer composites in railway brake blocks and the lack of studies on the synergistic effect of iron sand and Hollow Glass Microsphere (HGM) fillers under the SNI 8832:2019 standard. The study evaluates the impact of HGM volume fraction variations on composite hardness and wear rate. A quantitative experimental approach was employed using hand lay-up fabrication, combining an epoxy resin matrix, 15% iron sand, and varying HGM fractions (10%, 15%, 20%). Mechanical characterizations involved Shore D Durometer and Pin-on-Disc Tribometer tests. Results showed that HGM addition caused a statistically insignificant decrease in hardness, remaining well within the SNI 8832:2019 standard range. Conversely, increased HGM significantly reduced the specific wear rate, drastically improving wear resistance. In conclusion, while meeting hardness limits, the composite’s excessively high wear resistance requires further compositional modification to function ideally as a consumable friction material.